Impact of Crocin Supplementation on Serum level of Zinc, Coppe, and Magnesium levels in Individuals with Metabolic Syndrome - Maryam Saberi-Karimian; Parisa Asadiyan-Sohan; Sahar Ghoflchi; Maryam Ghasemi; Gordon A. Ferns; Malihe Aghasizadeh; Majid Ghayour-Mobarhan (Journal of Cardio-Thoracic Medicine)
Introduction and Objectives: Current evidence on the association between serum trace element levels and the development of Metabolic Syndrome (MetS) is limited and inconsistent. Recently, investigators have examined saffron supplementation that, which could increase serum trace elements in individuals with MetS. This paper will focus on determining the impact of crocin capsules on the effectiveness of serum Zn, Cu, and Mg in people diagnosed with MetS.Methods: In this study, a double-blind clinical trial was a conducted, comprising 44 individuals with MetS aged18-70 years.  Patients were categorized into a treatment group receiving crocin capsules (1g/day) or a placebo group for a period of 30 days. Levels of serum Zn, Mg, and Cu were measured using an automated analysis system (Model BT3000, Nica Instruments Biotech, Rome, Italy) at the baseline and end of the study.Results: Forty-four subjects completed the clinical trial. The investigation showed that baseline characteristics revealed no notable differences between the placebo and crocin groups (p > 0.05). According to our analysis, it was visibly apparent that there was an increase in serum Zinc levels following crocin supplementation for 30 days. Crocin supplementation had no significant effects on serum. Mg, Zn/Cu, or Cu concentrations.Conclusion: Metabolic disorders can be modulated by increasing the supply of dietary compounds with antioxidant properties such as crocin.